The Impact of Product Quality, Halal Lifestyle, and Promotion on Purchase Decisions for Thrift Products: The Mediating Role of Purchase Interest: Case Study in Muslim Communities in Cities Salatiga - Deden Rahayu Septiawan; Iskandar (Universitas Islam Negeri (UIN) Salatiga, 2024)
This research aims to determine the influence of product quality, halal lifestyle and promotion on purchasing decisions with purchase intention as an intervening variable (case study of Muslim communities in Salatiga City). This research uses quantitative methods with a research sample of 100 respondents from the people of Salatiga City using purposive sampling. Analysis includes instrument tests, statistical tests, classical assumption tests and path analysis. The results of this research show that: product quality, halal lifestyle and promotion partially have a positive and insignificant effect on purchasing decisions. Product quality has a significant positive effect on purchase interest, promotion has a positive but not significant effect on purchase interest, and halal lifestyle has an insignificant negative effect on purchase interest. The purchase interest variable has a positive and significant effect on purchasing decisions. Testing path analysis found that purchasing interest can mediate the influence of product quality on purchasing interest and the influence of promotions on purchasing decisions, but cannot mediate the influence of halal lifestyle on purchasing decisions.